Investigating the Assessment Literacy of Teachers in Private Junior High Schools in the Philippines - Clores, Michael Aguirre; Reganit, Arnulfo Aaron Ricafort (Humanities, Arts and Social Sciences Studies, 2020)
Increasingly, education in all levels in many institutions moves toward societal accountability mechanisms through reforms in assessment practices. Unless teacher’s assessment literacy is understood, how assessment practices influence students’ study strategies and learning processes remains a phenomenon. This study investigated the level of assessment literacy among junior high school level (Grade 7-10) teachers (n=241) in the Philippines. It also examined how teachers’ attributes affect their level of assessment literacy. The 35-item assessment literacy inventory and Item Facility (IF) index were used. General Linear Model (GLM) was done to predict teacher’s literacy level. Results showed that overall, the Grade 7-10 teachers have a “midlevel” literacy in assessment (M ± SEM = 17.15 ± 0.24). Teachers are most literate on “Developing assessment methods” while they are least literate on “Communicating assessment results.” Teachers desire to develop innovative forms of assessments for formative and summative classroom purposes but deterrence on communicating results of assessment to the students and parents suggest an uneven intention and conception of assessment for school accountability purposes. The Humanities, Arts and Social Sciences teachers were outperformed by the Mathematics and Science teachers based on their scores in the test. Mathematics and Science teachers are more literate in assessment than the other teachers. Among the categorical predictors, only the teacher’s content area could predict the teachers’ assessment literacy level. The findings point to teachers’ mixed understanding that assessment of student learning is an essential component of effective educational accountability system.